2021
DOI: 10.1186/s12889-021-11807-4
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter study of short-term changes in mental health emergency services use during lockdown in Kitchener-Waterloo, Ontario during the COVID-19 pandemic

Abstract: Background The COVID-19 pandemic and subsequent lockdown measures have led to increasing mental health concerns in the general population. We aimed to assess the short-term impact of the pandemic lockdown on mental health emergency services use in the Kitchener-Waterloo region of Ontario, Canada. Methods We conducted an observational study during the 6-month period between March 5 and September 5, 2020 using National Ambulatory Care Reporting Syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
3
9
0
Order By: Relevance
“…This pattern may reflect a habituation of the system and its users to the pandemic situation. As in this study, other health systems experienced worse outcomes as a consequence of the reduced mental health services ( 18 , 30 , 36 , 38 ). Alarmingly, many particularly vulnerable and precarious groups were especially affected ( 18 , 39 ).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…This pattern may reflect a habituation of the system and its users to the pandemic situation. As in this study, other health systems experienced worse outcomes as a consequence of the reduced mental health services ( 18 , 30 , 36 , 38 ). Alarmingly, many particularly vulnerable and precarious groups were especially affected ( 18 , 39 ).…”
Section: Discussionsupporting
confidence: 50%
“…Similar to this study, studies in several other regions, including the UK, Italy, Spain, Denmark, Switzerland, Australia, Canada, and the US, observed an overall decrease of inpatient admissions but an increase in involuntary admissions and more acute cases ( 4 , 26 35 ). Most regions reported reduced utilization for affective and anxiety disorders, but often no change for psychotic and sometimes addiction disorders ( 36 , 37 ). Similarly, despite often much higher COVID-19 incidences, service restrictions were much less pronounced in the second high incidence phase in winter 2020–2021 than in the first such phase in spring 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to this study, studies in several other regions, including the UK, Italy, Spain, Denmark, Switzerland, Australia, Canada, and the US, observed an overall decrease of inpatient admissions but an increase in involuntary admissions and more acute cases (4,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Most regions reported reduced utilization for affective and anxiety disorders, but often no change for psychotic and sometimes addiction disorders (36,37). Similarly, despite often much higher COVID-19 incidences, service restrictions were much less pronounced in the second high incidence phase in winter 2020-2021 than in the first such phase in spring 2020.…”
Section: International Comparisonsupporting
confidence: 85%
“…In addition, the same study found that children with autism spectrum disorders experienced worsening mental health mostly due to changes in routine demonstrating the impact of social restrictions on vulnerable populations of society (O’Sullivan et al, 2021). Even where researchers documented a decrease in mental health emergency department visits and crisis calls throughout the first wave of the pandemic, they acknowledge that data may present differently if collected over a longer period as an accumulation of stress, loneliness, isolation, and other factors may have taken longer to develop (Dainton et al, 2021). With respect to Canadian data, Statistics Canada’s Survey on COVID-19 and Mental Health (SCMH) showed that the proportion of Canadian adults screening positive for major depressive disorder (MDD) increased from 15% in fall 2020 to 19% in spring 2022 (Statistics Canada, 2021).…”
Section: Introductionmentioning
confidence: 99%